Influence of A.C. Frequency on Hollow Magnetron Sputtering Discharge Parameters - Hasan, Zahraa Mohammed; Abbas, Qusay Adnan (Iraqi Journal of Physics, 2024)
In the present work, optical emission spectroscopy was used to diagnose the influence of A.C. power source frequency on the hollow magnetron sputtering discharge parameters (such as discharge emission, discharge current and voltage, glow discharge structure, temperature (Te) and electron number density (ne), Debye length (λD), and plasma parameter (ND) of constant pressure. The electron temperature and number density were determined using the Boltzmann plots and the Stark broadening methods, respectively. The results illustrate that the normal glow discharge structure is similar to the D.C. discharge mode. The magnetic field has no impact on the fundamental discharge parameter in both A.C. frequencies under study. On the other hand, the other discharge parameters (Te, ne, λD and ND) increase with increasing the magnetic field in both discharge frequencies. In addition, the increase in the frequency of the A.C. source current led to an increase in the discharge intensity emission and the other discharge parameters being studied. In this case, in frequency 7 kHz, Te surged from 0.685 eV to 0.839 eV, and ne experienced an increase from 3.088 x 1018 m-3 to 4.902 x 1018 m-3. At a frequency of 9 kHz, the electron temperature surged from 0.711eV to 0.911 eV. ne experienced an increase from 3.615 x 1018 m-3 to 6.749 x 1018 m-3.